Competency‐based curriculum transition: A conceptual framework. Issue 2 (21st December 2020) - Carlgren, Dave
Abstract: As the 21st century has just passed its 20th year, there have been some changes to educational policy and practice in domains in many countries around the world, including more than 4.1 million children in 137 countries participating in skill development programmes aimed at fundamental learning. Few of these have reached to secondary schools. The primary goal of this article was to present aspects of a framework that may be useful in designing curriculum to incorporate competencies to make changes to existing educational practice. The considerations presented are not knew to those with existing competency‐based education (CBE) frameworks, the orienting aspects of Integral Theory may provide some insights for ideal CBE implementation. Why is it that high schools globally are not adopting CBE within their districts? With the majority of the world population in China and India following traditional models of educational practice, perhaps a clear explanation of the necessary considerations for the implementation of CBE has not been represented. It is worthy of note that, based on research results, the majority of the educational reform in both of these populous nations occurs at the postsecondary level. As an attempt to encompass all that is required for an ideal implementation of CBE, three interconnected sets of recommendations are made as areas of implementation focus: ensuring a learner focus and various pathways from a Policy perspective, feedback and the role of the teacher from the Practice level, and communication from the Process level.